Assessment of sural flap microcirculation: Which position maintains the optimal perfusion?. Issue 4 (April 2016) - Rothenberger, Jens; Krauss, Sabrina; Held, Manuel; Tschumi, Christian; Rahmanian-Schwarz, Afshin; Schaller, Hans-Eberhard; Jaminet, Patrick
Summary: Background: Limb elevation is a commonly used approach for reducing edema and increasing venous drainage. Considering the anatomy of the sural flap with retrograde perfusion and hence potentially difficult blood outflow, the best angle for positioning the leg following operation is not yet known. Methods: A total of 14 patients undergoing sural flap lower limb reconstruction were enrolled in the study. We assessed the perfusion dynamics of the flaps using the oxygen-to-see (O2C) device that combines laser light, to determine blood flow, and white light to determine the relative amount of hemoglobin and oxygen saturation. Three different positions were evaluated: 45° angle downward, the horizontal position, and 45° angle upward. Results: The blood flow was significantly higher in the 45° upward position compared to the 45° downward position. The relative amount of hemoglobin was significantly lower in the 45° upward position compared to the 45° downward position. No significant differences with regard to oxygen saturation were observed. Conclusion: The results of this study show a more precise pattern of perfusion due to different positioning. The 45° upward position of the leg generally maintains the best blood flow and venous drainage. However, compared to horizontal positioning, these differences were not statistically significant. As an elevation of 45° can be uncomfortable for patients, we recommend an elevation of the leg which approximates the 45° upward position but is still comfortable.